ЯЗЫКИ И КУЛЬТУРЫ ПРЕДСТАВИТЕЛЕЙ ОСНОВНЫХ ЭТНОСОВ КАЗАХСТАНА ЧЕРЕЗ ПРИЗМУ КАЗАХСТАНСКОЙ МОДЕЛИ МЕЖЭТНИЧЕСКОГО СОГЛАСИЯ - А.Т. Абдулина (Asian Journal "Steppe Panorama", 2025)
In sovereign Kazakhstan, a purposeful state policy is being carried out to form a unified Kazakh people on the basis of a single Kazakh identity while preserving linguistic and cultural pluralism. Ethnopolitics strengthens interfaith and interethnic harmony as the basis of national security. The state policy of the development of the Kazakh language, migration and demographic processes have led to the approval of a general trend in the field of the education system for a gradual increase in the number of students and schools with the Kazakh language of instruction. Representatives of large ethnic groups of Kazakhstan also have the opportunity to receive secondary education in their native languages, but the process of reducing national schools is increasing, causing discontent among many ethnic groups. During the ethno-linguistic processes, the formation of a bilingual social and communicative space with the predominance of Kazakh and Russian languages is observed. However, the presence of contradictions in the language sphere, national-linguistic dissatisfaction on the part of non-indigenous ethnic groups remains the main conflict-causing factor in the republic. In the field of media, the Kazakh language has begun to compete with the Russian language, which has a significant political resource, but it is necessary to expand the rights of ethnic minorities to access media broadcasting in their native languages. Great work on the preservation and development of ethnic cultures is carried out by the Assembly of the People of Kazakhstan and regional and national cultural centers.